Oh **UK! Whatever next? Multimodal humour on Brexit-related covers of The Economist - Miller, Dorota (Studia Anglica Posnaniensia, 2023)
Brexit has undoubtedly been one of the most hotly debated topics in both European and world politics, setting a precedent in the history of European integration. Despite its unquestionably serious repercussions, a considerable part of Brexit media coverage was aimed at amusing the audience. An example of this includes Brexit-related covers of The Economist. The following paper looks at humour through the lens of the traditional incongruity theory reaching back to Aristotle. Humorous effects are examined and elucidated from a multimodal perspective, including both the visual and verbal layer of the covers and their interplay, as well as intertextual techniques relying on echoing artefacts of the verbal and visual culture. The data for the study were collected over the span of approximately four years, between June 2016 (the EU referendum) and February 2020 (Brexit). The empirical section of the study seeks to distil the prevailing trends among the humorous covers focusing on Brexit, paying due attention to the specificity of the genre (magazine cover) and the political background of the topic in question. The intermodal and intertextual relationships involved in creating humour are examined and categorised into the following major types: analogy, addition/extension, antithesis, ambiguity, and allusion/appropriation.